Transvaginal oestrogen therapy – only for postmenopausal women? - Tomaszewski, Jacek (Menopause Review/Przegląd Menopauzalny, 2008)
Many women suffer considerably from urogynaecological symptoms caused by hypoestrogenism. Application of topical oestrogens in young women improves the function of the urogenital tissues, facilitating the restoration of a normal vaginal environment and augmenting the antimicrobial defence. Topical oestrogens prevent the development of urogenital atrophy during breastfeeding and after oncological and immunosuppressive treatment; they also enable optimal preparation of anatomical structures before surgery and promote wound healing and integration of surgical materials with host tissues, which decrease the risk of implant rejection.